2013
DOI: 10.1091/mbc.e12-08-0626
|View full text |Cite
|
Sign up to set email alerts
|

SHIP2 regulates epithelial cell polarity through its lipid product, which binds to Dlg1, a pathway subverted by hepatitis C virus core protein

Abstract: HCV core induces loss of polarity and down-regulates SHIP2 and Dlg1 expression. SHIP2 and PtdIns(3,4)P2 are localized at the basolateral membrane of polarized cells. SHIP2 siRNA and its catalytically inactive mutant disrupt epithelial polarity, and SHIP2 rescues core-induced loss of polarity through RhoA activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 75 publications
(47 reference statements)
4
58
0
1
Order By: Relevance
“…In polarized epithelial cells, PtdIns(3,4,5)P 3 and PI3Ks are mainly present on the basolateral membrane 21 while PTEN plays a central role in the formation of the apical membrane 22 . We have recently reported that SHIP2 is present at the basolateral membrane and regulates cell polarization 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In polarized epithelial cells, PtdIns(3,4,5)P 3 and PI3Ks are mainly present on the basolateral membrane 21 while PTEN plays a central role in the formation of the apical membrane 22 . We have recently reported that SHIP2 is present at the basolateral membrane and regulates cell polarization 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NS4B protein induces lipogenesis in infected cells by activating the Akt pathway[49]. It has been shown that HCV core protein is expressed at the basal membrane of polarized cells, which leads to a deregulation of actin organization and affects focal contacts by increasing the expression of phosphorylated paxillin at the basal membrane[50]. The same study showed that the deregulation of actin is due to RhoA inhibition and Rac1 activation in cells expressing HCV core protein.…”
Section: Pi3k Activity Cell Polarity and Hcv Infectionmentioning
confidence: 99%
“…This work focused on virus entry and replication and the epithelial to mesenchymal transition, but the effect of PI3K expression on the loss of cell polarity induced by HCV infection was not investigated. Nevertheless, the phenotype of cysts from MDCK cells expressing HCV core protein was of a multi-lumen type[50] which differed markedly from that of the inverted polarity cysts obtained from MDCK cells treated with the p100δ inhibitors IC87114 and CAL-101, but was similar to those from MDCK cells treated with the p110γ and p110β inhibitors AS-605240 and TGX115, respectively[41]. This observation reveals a potential role for p110γ and p110β in the loss of cell polarity induced by HCV infection.…”
Section: Pi3k Activity Cell Polarity and Hcv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Par protein is liver kinase b1 (Lkb1, or Par4), which phosphorylates and activates a family of AMP-activated protein kinases to regulate cell growth, metabolism and polarity 1. Class I isoforms of phosphoinositide 3-kinases (PI3K)3 and their antagonising phosphatases phosphatase and tensin homologue4 (PTEN)) and SH2 domain containing inositol 5-phosphatase 25 (SHIP2) are crucial determinants of apicobasal polarity (figure 1A).…”
mentioning
confidence: 99%